PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT. Varia Usaha Beton Cabang Rembang) - Lestari, Diana; Suryandani, Wulan; Sunarto, Sunarto (JAB (Jurnal Akuntansi & Bisnis), 2017)
Performance or work performance is the result of work, quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This study aims to test and prove the influence of leadership style (X1), motivation (X2), work environment (X3), organizational culture (X4) and effectiveness of implementing accounting information systems (X5) on employee performance (Y).The data collection technique used in this study is to use the survey method, namely by using a questionnaire. The sampling technique used in this study was sampling census. The number of samples used in this research are all employees of PT. Varia Usaha Beton Cabang Rembang with 40 employees.Â Based on the results of research at PT. Varia Usaha Beton Cabang Rembang, partial test / t test conducted shows that the leadership style variable has a positive and insignificant effect on employee performance, the motivation variable has a positive and insignificant effect on employee performance, the work environment variable has no significant positive effect on employee performance, organizational culture variable no significant positive effect on employee performance, and the effectiveness of the application of accounting information systems has a significant positive effect on employee performance. While the f test shows that the variables of leadership style, motivation, work environment, organizational culture, and effectiveness variables of the application of accounting information systems simultaneously have a significant positive effect on employee performance.Â Keywords: Leadership Style, Motivation, Work Environment, Organizational Culture, Effectivenes of Application of Accounting Information Systems, Employee Performance